The Relationship of Knowledge With The Self-Management of Diabetes Clients Diabetes Mellitus - Untung Halajur; Irfan Setiawan (Publisher Cv. Inara, 2021)
Knowledge or cognitive domain is very important for the formation of a person's actions. Knowledge is the main basis for treatment and prevention of diabetes perfect. Someone who has less knowledge about diabetes mellitus will be difficult to prevent the occurrence of diabetes and if a person suffering from diabetes with less knowledge will easily suffer complications of diabetes. Identifying Knowledge Relationships with Self-Management Patient Diabetes Militus in Poli Disease dr. Doris Sylvanus Palangkaraya. This research is quantitative questionnaires. The study design used in the form of cross-sectional analysis, the measurement and data collection only at one time.Measured variables, namely the relationship between knowledge as independent variables and self-management of diabetes mellitus as the dependent variable. Results of the analysis above shows respondents who have a good knowledge with good self-management (82.2%). While knowledge is good with a poor self-management amounted to (17.8%). The results of the analysis the table showed there (48.1%) who had a poor knowledge with good self-management. While knowledge was poor with poor self-management amounted to (51.9%). This study suggests knowledge of Diabetes Militus patients in Poli Disease dr. Doris Sylvanus Palangkaraya in getting significant value p-value of 0.002 or <0.05 that means there is a close relationship between knowledge and self-management of patients with diabetes mellitus.